Attachment and Identity Formation in Bicultural Families - Dezhan, Seyed Sajad; Setayesh Manesh, Ebrahim; Zebardasti, Kimiya; Parsadost, Vale Mohammad; Derakhshandeh, Mansour (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: This study aims to explore the dynamics of attachment and identity formation within bicultural families, focusing on the unique challenges and opportunities they face. The research seeks to understand how parenting styles, bonding activities, emotional connections, and the role of extended family influence these processes. Additionally, the study examines the continuous cultural negotiation and the impact of social relationships and support systems on the overall well-being of children raised in bicultural environments. Methods: A qualitative research design was employed, utilizing semi-structured interviews to gather in-depth data from 23 participants, including parents and children from 15 bicultural families. The participants were selected through purposive sampling to ensure diverse cultural backgrounds. Data were analyzed using NVivo software, with themes and patterns identified through rigorous coding and thematic analysis. Theoretical saturation was reached after conducting interviews with the 15 families, ensuring comprehensive coverage of the study’s objectives. Results: The study identified four main themes: Attachment Dynamics, Identity Formation, Cultural Negotiation, and Family and Social Relationships. Attachment dynamics were influenced by varied parenting styles and the integration of cultural practices. Identity formation was shaped by cultural pride, school environment, and peer relationships. Cultural negotiation involved continuous adaptation of decision-making processes, traditions, and language practices. Family and social relationships, including peer interactions and community engagement, played a crucial role in supporting the social experiences of bicultural children. Conclusion: The findings highlight the complex interplay of attachment and identity formation in bicultural families. Effective parenting, cultural negotiation, and strong social support systems are essential for fostering positive identity development and family cohesion.